THERAPEUTIC CLIMBING IN REHABILITATION: A NARRATIVE REVIEW - Władysław Hryniuk,; Julia Kwiecińska,; Jacek Sitkiewicz,; Alicja Toczyłowska,; Mateusz Muras,; Łukasz Bialic,; Lidia Mądrzak,; Marta Korchowiec,; Wiktor Chrzanowski,; Katarzyna Krzyżanowska, (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and objective: Climbing has recently emerged as a promising form of movement therapy, combining physical and psychological benefits. This review aims to provide a comprehensive overview of current evidence regarding the therapeutic application of sport climbing—particularly bouldering and top-rope climbing—in rehabilitation settings. It focuses on its use in treating postural defects, neurological disorders, psychiatric conditions, and developmental disorders in children.Review methods: The review is based on studies retrieved from PubMed, Google Scholar, ResearchGate, and other scientific databases. Included materials comprise clinical and preclinical studies, randomized trials, case reports, and reviews related to the use of sport climbing in rehabilitation.State of knowledge: Therapeutic climbing has demonstrated benefits across diverse clinical populations, including individuals with chronic low back pain, scoliosis, multiple sclerosis, Parkinson’s disease, traumatic brain injury, cerebral palsy, ADHD, and autism spectrum disorders. Reported outcomes include improved balance, coordination, muscle strength, proprioception, mood regulation, and cognitive function. Climbing is also associated with enhanced motivation and social integration. However, limitations remain, such as the lack of standardised protocols, a scarcity of high-quality RCTs, and limited long-term data.Conclusion: Climbing integrates physical exertion, neuromotor coordination, and emotional engagement, making it a multifaceted rehabilitation tool. Its ability to promote neuroplasticity and whole-body engagement suggests significant untapped potential. Nonetheless, to validate its clinical utility and ensure safety, there is a need for robust, standardised research and structured implementation protocols supervised by qualified professionals.